Genome Sequence of Ruloma Virus, a Novel Paramyxovirus Clustering Basally to Members of the Genus Jeilongvirus - Vanmechelen, Bert; Meurs, Sien; Zisi, Zafeiro; Goüy de Bellocq, Joëlle; Bletsa, Magda; Lemey, Philippe; Maes, Piet (Microbiology resource announcements, 2021)
We report here the complete genome sequence of ruloma virus, a novel paramyxovirus detected in a Machangu's brush-furred rat from Tanzania. Ruloma virus has the longest orthoparamyxovirus genome reported to date and forms a sister clade to all currently known members of the genus Jeilongvirus.